Dos aproximaciones a la marginalidad: Los pescadores en Las redes del mar y Chiloé, cielos cubiertos - Sanhueza, María Teresa (Latin American Theatre Review, 2004)
This study compares two plays written in Chile, Las redes del mar by José Chesta and Chiloé, cielos cubiertos by María Asunción Requena. Chesta and Requena consciously decided to put on stage characters that are part of a marginalized sector of society: fishermen and their families. Chesta and Requena write "social plays" in which they communicate the lack of opportunities that fishermen encounter when trying to break the cycle of poverty in which they have lived for many generations. Both playwrights show the social and personal problems faced by the members of this community and try to call the spectators’ attention to them. (MTS, in Spanish)